A zinc(II) tetraphenylporphyrin peripherally functionalized with redox-active "trans-[(η5-C5H5)Fe(η5-C5H4)CC](κ2-dppe)2Ru(CC)-" substituents: Linear electrochromism and third-order nonlinear optics. (28th January 2015) - Merhi, Areej; Grelaud, Guillaume; Ripoche, Nicolas; Barlow, Adam; Cifuentes, Marie P.; Humphrey, Mark G.; Paul, Frédéric; Paul-Roth, Christine O.
Abstract : Graphical abstract: The synthesis and characterization of a new Zn(II) tetraphenylporphyrin derivative (4 ) featuring eight redox-active centers at the periphery (four trans -Ru( κ 2 -dppe)2 fragments and four ferrocenyl endgroups) is reported, and its linear spectroelectrochemistry and third-order nonlinear optical properties at 560 nm and 630 nm are discussed. Abstract: A nonametallic organometallic-coordination complex (4 ), assembled from redox-active ferrocenyl (Fc) and Ru( κ 2 -dppe)2 fragments (dppe = 1, 2-bis(diphenylphosphino)ethane) as peripheral donor groups and a central Zn(II) tetraphenylporphyrin (ZnTPP) core, has been prepared and characterized. Complex4 is obtained in one step from a pentametallic organometallic porphyrin precursor following substitution of the peripheral chloride ligands by ferrocenylalkynyl moieties (CCFc). The spectroelectrochemistry of4, and that of previously reported porphyrins featuring related peripheral electron-rich d 6 -transition metal alkynyl units, has been investigated; the optical and redox properties of4 are briefly discussed, and its potential, and that of a related pentanuclear tetraferrocenyl ZnTPP complex, to function as redox-switchable chromophores is examined. Preliminary studies of the cubic NLO properties of4 have been undertaken by Z -scan studies at 560 nm and 630 nm, the results from which are also reported.